Plastic failure and deformation calculation of shaft structure in soil under lateral explosion - Shanzheng Sun; Yuan Liu (Scientific Reports)
Abstract This study investigated the failure phenomenon of steel plate-reinforced concrete shaft structures situated in soil under medium-field explosions. Through model experiments and finite element numerical simulations, we analyzed the process of plastic hinge line formation and the deformation characteristics of the structure, and the dimensionless circumferential relative displacement α 1 was proposed as an index to measure the structural deformation. According to the damage characteristics, the structural failure modes were divided into standard failure mode and three extension failure mode. The empirical formula of the characteristic size of plastic hinge line is derived from the numerical simulation data. Based on the numerical simulation data and the law of conservation of energy, the empirical formula of the characteristic size of the plastic hinge line was obtained by fitting, the motion field of each plate in the plastic hinge line was analyzed, and the calculation method of the rigid plastic deformation of the shaft structure was established. We compared the discrepancies between the finite element calculation model and the theoretical algorithm and examined the impacts of concrete strength, concrete thickness to radius ratio, steel plate thickness to radius ratio, and charge mass on steel plate displacement. The results showed that increasing concrete strength and the thicknesses of both concrete and steel plates improved the structure’s blast resistance and reduced deformation. And at the same scaled explosive distance, a higher charge mass increased the distance to the structure, leading to greater external work and structural deformation. In cases where concrete thickness to radius ratio greater than 13%, the relative error between theoretical calculations and numerical simulations was below 20%, indicating the computational method’s accuracy in predicting the deformation of steel plate-reinforced concrete shaft under medium-field explosions.